DETERMINANTS AFFECTING THE PERFORMANCES OF THE VIETNAMESE ENTERPRISES IN THE FIELD OF ELECTRONICS AND ELECTRICAL HOUSEHOLD APPLIANCES WHEN VIETNAM JOINS THE TPP - Tran Phi Hoang , Nguyen Thi Van , Luong Thi Minh Huong , Ha Trong Quang (International Journal of Research Science and Management, 2016)
The study is to analyze the factors affecting the performances of Vietnamese enterprises in the field of electronics and electrical household appliances. The authors used qualitative and quantitative research methods that are combined to conduct with 201 consumers 30 observed variables. The study results showed that there are 5 factors impacting on sales performances as follows: Sales Skill, Tangibles, Customer services, Reliability and Service process with significance level 5 %. In addition, the research results processed from SPSS 20.0 software. The result was also a scientific evidence and important for researchers, and polic y makers who apply them for improving the performance for Vietnamese enterprises in the future. The researcher had obtained the main objectives of this study were to: 1. The researchers were to identify and test some factors affecting the performances of Vietnamese enterprises in the field of electronics and electrical household appliances. 2. The researchers had recommendations to improve the performances of Vietnamese enterprises in the field of electronics and electrical household appliances.